2014
DOI: 10.3109/13625187.2014.971454
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine device insertion in the postpartum period: A systematic review

Abstract: This review supports the evidence that insertion of an intrauterine contraceptive within the first 48 hours of vaginal or caesarean delivery is safe. Expulsion rates should be further studied in larger randomised controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
3
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 12 publications
3
63
3
7
Order By: Relevance
“…As expulsions are infrequent after this period, frequent sonography is not recommended. Our findings are in keeping with other reports where a significant proportion of expulsions occurred in the first 3 months after IUD insertion 9 11. Marchi et al 12.…”
Section: Discussionsupporting
confidence: 93%
“…As expulsions are infrequent after this period, frequent sonography is not recommended. Our findings are in keeping with other reports where a significant proportion of expulsions occurred in the first 3 months after IUD insertion 9 11. Marchi et al 12.…”
Section: Discussionsupporting
confidence: 93%
“…Attendance rates at the 6-week postpartum visit are variable, with as many as 33% of prenatal care recipients not returning for postpartum care (1). Postplacental IUD insertion, which refers to IUD insertion within 10 minutes of placental delivery is one potential way to decrease rapid repeat pregnancies (2). However, expulsion rates are as high as 27% at 6 months postpartum with postplacental IUD insertion, compared to 1–4% with interval insertion at four to 6 weeks after delivery (37).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the limitations of this small study, the high discontinuation and pregnancy rates among our cohort highlight the difficulties that postnatal women, particularly, have in sustaining contraception utilisation in country settings like South Africa. IUD expulsion occurred in one-third of users in this follow-up study, which might be explained by the study limitations; however, this does not appear to be extraordinarily high: a 2015 systematic review of postnatal IUD insertion found IUD expulsion rates ranging from 2.4% to 72% across a variety of study designs 4. This suggests that some high-quality research is needed to clarify the risk of IUD expulsion for postnatal IUD users.…”
mentioning
confidence: 74%